2009
DOI: 10.1002/art.24876
|View full text |Cite
|
Sign up to set email alerts
|

Classification, presentation, and initial treatment of Wegener's granulomatosis in childhood

Abstract: Methods. Eligible patients had been diagnosed by site rheumatologists (termed the "MD diagnosis") since 2004. This diagnosis was used as a reference standard for sensitivity and specificity testing of the 2 WG classification criteria. Descriptive analyses were confined to ACR-classified WG patients.Results. MD diagnoses of 117 patients (82 of whom were female) were WG (n ‫؍‬ 76), microscopic polyangiitis (n ‫؍‬ 17), ANCA-positive pauci-immune glomerulonephritis (n ‫؍‬ 5), Churg-Strauss syndrome (n ‫؍‬ 2), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
139
3
12

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(165 citation statements)
references
References 21 publications
9
139
3
12
Order By: Relevance
“…Less commonly, findings of musculoskeletal, gastrointestinal, opthalmic, cutaneous and neurological involvement are observed. Cardiac involvement has not been found in any patient (39). In the study conducted by Bohm et al (40), the otorhinolaryngological findings were reported to include septum perforation, saddle nose, auricular chondritis, subglottic stenosis, coarse voice and stridor.…”
Section: -Vasculitides Which Involve Small Vessels A-anti Neutrophilmentioning
confidence: 87%
See 1 more Smart Citation
“…Less commonly, findings of musculoskeletal, gastrointestinal, opthalmic, cutaneous and neurological involvement are observed. Cardiac involvement has not been found in any patient (39). In the study conducted by Bohm et al (40), the otorhinolaryngological findings were reported to include septum perforation, saddle nose, auricular chondritis, subglottic stenosis, coarse voice and stridor.…”
Section: -Vasculitides Which Involve Small Vessels A-anti Neutrophilmentioning
confidence: 87%
“…Characteristic findings related with involvement of these organs have been identified in studies conducted with children (39,40). The most common findings at the time of onset of the disease include fatigue, wieght loss and fever and otorhinolaryngological, respiratory system and renal findings are the most commonly observed findings.…”
Section: -Vasculitides Which Involve Small Vessels A-anti Neutrophilmentioning
confidence: 99%
“…No clinical trials have been conducted in pediatric AAV, and almost all knowledge about optimal treatment and outcomes has been extrapolated from adult studies or collected from small case series. Pediatric patients are often given remission-induction treatment with corticosteroids and cyclophosphamide [33]. Rituximab is recommended in refractory or relapsing disease [33].…”
Section: Pediatric Considerationsmentioning
confidence: 99%
“…Pediatric patients are often given remission-induction treatment with corticosteroids and cyclophosphamide [33]. Rituximab is recommended in refractory or relapsing disease [33]. Methotrexate, mycophenolate mofetil, or azathioprine is often used in maintenance therapy [33,34].…”
Section: Pediatric Considerationsmentioning
confidence: 99%
See 1 more Smart Citation